2002
DOI: 10.1093/jnen/61.11.1013
|View full text |Cite
|
Sign up to set email alerts
|

Broad Expression of Toll-Like Receptors in the Human Central Nervous System

Abstract: The family of Toll-like receptors (TLRs) plays a key role in controlling innate immune responses to a wide variety of pathogen-associated molecules. In this study we investigated expression of TLRs in vitro by purified human microglia, astrocytes, and oligodendrocytes, and in vivo by immunohistochemical examination of brain and spinal cord sections. Cultured primary microglia were found to express mRNA encoding a wide range of different TLR family members while astrocytes and oligodendrocytes primarily express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
791
2
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 874 publications
(836 citation statements)
references
References 26 publications
22
791
2
5
Order By: Relevance
“…Our results, however, indicate that the primary signaling pathway for IFN-b induction activated by dsRNA functions via RIG-I/ MDA5 in the cytoplasm but not via TLR3 expressed on the cell surface or in endosomes. This is contrary to results obtained for other types of epithelial cells, such as bronchial epithelial cells and endometrial cells, in which surface TLR3 recognizes viral dsRNA to signal the presence of infection via the TLR3-IRF3-type I interferon signaling pathway [9,11,12,15]. Here we discuss dsRNAsensing system functioning in HIBECs and the role of high expression levels of TLR3 in diseased livers.…”
Section: Introductioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Our results, however, indicate that the primary signaling pathway for IFN-b induction activated by dsRNA functions via RIG-I/ MDA5 in the cytoplasm but not via TLR3 expressed on the cell surface or in endosomes. This is contrary to results obtained for other types of epithelial cells, such as bronchial epithelial cells and endometrial cells, in which surface TLR3 recognizes viral dsRNA to signal the presence of infection via the TLR3-IRF3-type I interferon signaling pathway [9,11,12,15]. Here we discuss dsRNAsensing system functioning in HIBECs and the role of high expression levels of TLR3 in diseased livers.…”
Section: Introductioncontrasting
confidence: 58%
“…TLR3 is localized to endosomes and/or the cell surface in epithelial cells, while RIG-I/MDA5 resides in the cytoplasm [3][4][5]. TLR3-expressing epithelial cells are widely distributed throughout the body, with prominent expression in intestinal, cervical, uterine, endometrial, bronchial, and corneal epithelial cells, the central nervous system, and epidermal keratinocytes [6][7][8][9][10][11][12][13][14][15][16]. The function of TLR3 has been intensively studied in some of these epithelial cells; bronchial epithelial cells recognize dsRNA by cell-surface TLR3 and induce cellular responses, including the secretion of type 1 interferon (IFN) via the Toll-IL-1R homology domain-containing adaptor molecule 1 (TICAM-1)-interferon regulatory factor 3 (IRF3) signaling pathway [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Although grampositive pathogens are common etiologic agents of CNS bacterial infections (Mathisen and Johnson, 1997;Townsend and Scheld, 1998), the innate immune mechanisms elicited by these organisms in microglia still remain to be completely defined. In the CNS, microglia likely play an essential role in initiating innate immunity through their extensive expression of PRRs including TLRs and CD14 (Bsibsi et al, 2002;Dalpke et al, 2002, Kielian et al, 2002Laflamme et al, 2001;Olson and Miller, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…PAMPs are defined as invariant molecular motifs of bacteria, fungi, and viruses that are essential for pathogen survival and are conserved across broad subclasses of pathogens (Akira and Hemmi, 2003;Takeda et al, 2003). Studies have demonstrated that Toll-like receptors (TLR) are important for PAMP recognition, and microglia express the majority of TLRs identified to date (TLR1-9) (Bsibsi et al, 2002;Kielian et al, 2002Kielian et al, , 2005Laflamme et al, 2003;Olson and Miller, 2004), which, in theory, enables these cells to recognize a wide spectrum of PAMPs (Akira and Hemmi, 2003;Sieling and Modlin, 2002;Takeda et al, 2003). Recently, we reported the functional importance of TLR2 in mediating microglial activation in response to Staphylococcus aureus (S. aureus) and its cell wall component peptidoglycan (PGN) using primary microglia isolated from TLR2 knockout (KO) and wild-type (WT) mice (Kielian et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Microglia, the specialized immune cells in the brain, constitutively express a broad array of TLRs [4,5] . The most well-studied TLRs in microglia are TLR2 and TLR4 that are key players in neuroinfl ammation in CNS trauma and neurodegenerative disease [6] .…”
Section: Introductionmentioning
confidence: 99%